2003
DOI: 10.1080/09500340308234581
|View full text |Cite
|
Sign up to set email alerts
|

Phase-locking of multicore fibre laser due to talbot self-reproduction

Abstract: The multicore fibre laser (MCFL), containing an array of singlemode microcores in a circle inside the pump core, is a promising compact laser source. The problem is to synchronize the radiation of microcores with different propagation constants at a given radiation frequency. The theory of phaselocking of an MCFL with an external mirror and an annular waveguide matched to the multicore fibre and having a length some fraction of the Talbot distance is developed. Collective mode selection appears to occur due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 29 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…4 -6 It has been demonstrated that such annular dielectric waveguides can be fabricated with a femtosecond-pulse laser-writing technique, 7 and that their self-imaging ability can be applied in phase locking of a circular array of fiber lasers. 8,9 Theoretical studies dealing with the self-imaging phenomenon in annular-core fibers have, so far, been restricted to the domain of scalar optics by means of the weakly guiding approximation. 5,6,8 In such annular fibers, however, the approximation may not be very accurate, especially if the fiber core is very thin, and it has a large diameter.…”
Section: Introductionmentioning
confidence: 99%
“…4 -6 It has been demonstrated that such annular dielectric waveguides can be fabricated with a femtosecond-pulse laser-writing technique, 7 and that their self-imaging ability can be applied in phase locking of a circular array of fiber lasers. 8,9 Theoretical studies dealing with the self-imaging phenomenon in annular-core fibers have, so far, been restricted to the domain of scalar optics by means of the weakly guiding approximation. 5,6,8 In such annular fibers, however, the approximation may not be very accurate, especially if the fiber core is very thin, and it has a large diameter.…”
Section: Introductionmentioning
confidence: 99%
“…In the passive phase-locking approach, called self-phase locking, cophasing is obtained based on a coupling mechanism that can be realized by energy coupling (self-organization of the laser emissions) or nonlinear interactions effects [160,[225][226][227][228][229][230][231][232][233][234][235][236][237]. This approach is simple to design and operate.…”
Section: Passive Phase Controlmentioning
confidence: 99%
“…In the passive phase-locking approach, called self-phase locking, cophasing is obtained based on a coupling mechanism that can be realized by energy coupling (self-organization of the laser emissions) or nonlinear interactions effects [160,[225][226][227][228][229][230][231][232][233][234][235][236][237]. This approach is simple to design and operate.…”
Section: Passive Phase Controlmentioning
confidence: 99%